2019
DOI: 10.25100/cm.v50i2.4124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment and control of high blood pressure in the elderly according to the ethnic group. Colombian survey

Abstract: Introduction: High blood pressure (HBP) is the main cardiovascular risk factor, it is more prevalent in the older adult population, and the prevalence can vary between ethnic groups. Objective: To estimate the prevalence of HBP, knowledge, treatment and control in population aged ≥60 years, resident in Colombia, according to their ethnic condition. Methods: Population sample selected by multistage sampling. Ethnicity was defined based on skin color. HBP was defined as systolic blood pressure ≥140, and/or diast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
1
10
1
2
Order By: Relevance
“…21 Even so, the treatment rate of hypertension in the elderly population in Shenzhen was still far below that of elderly in other countries such as the USA, Australia, Germany and Colombia. [22][23][24] Similar to other studies, we found that the treatment of hypertension was significantly higher among older, ex-smokers, non-drinkers,higher education level and those engaging in physical activity. 9 19 24 25 Participants engaged in physical activity may generally pay more attention to their health.…”
Section: Results Of Multivariate Analysis Of Factors Associated With Treatment and Control Of Hypertensionsupporting
confidence: 88%
See 1 more Smart Citation
“…21 Even so, the treatment rate of hypertension in the elderly population in Shenzhen was still far below that of elderly in other countries such as the USA, Australia, Germany and Colombia. [22][23][24] Similar to other studies, we found that the treatment of hypertension was significantly higher among older, ex-smokers, non-drinkers,higher education level and those engaging in physical activity. 9 19 24 25 Participants engaged in physical activity may generally pay more attention to their health.…”
Section: Results Of Multivariate Analysis Of Factors Associated With Treatment and Control Of Hypertensionsupporting
confidence: 88%
“…Previous studies have revealed that being female had a statistically significant association with the control of hypertension. 24 25 On the contrary, our findings suggested that being female was a negative indicator of hypertension control, strongly indicating that it deserves further study. Our study revealed that participants with high educational attainment had more than 1.28-fold higher probability of being in control of their hypertension status than those with low educational level.…”
Section: Discussioncontrasting
confidence: 62%
“…22 The 2015 SABE survey also found that among people aged 60 years and older, the rate of controlled HBP was 44% and 54% in those in the subsidized and the contributive insurance, respectively. 4 There has been reported that people in the subsidized insurance are less likely to use preventive services and claim medicines. 27 , 35 , 36 These data may reflect that access barriers to medicines and other interventions in the subsidized insurance could account for the lower blood pressure control rates in this population.…”
Section: Discussionmentioning
confidence: 99%
“… 2 In Colombia, a low-middle income country (LMIC), the global prevalence of HBP estimated by the National Health Survey in 2007 was 22.8%, 3 and for those aged 60 years and older, the 2015 SABE survey reported a prevalence of 51.4% for men and 57.7% for women. 4 …”
Section: Introductionmentioning
confidence: 99%
“…43 Similarly, in a national study of over 20,000 older Colombians, 58% (95%CI 55 − 50) had hypertension. 44 Because hypertension is a modi able risk factor for most common causes of morbidity and mortality in older adults, these results highlight a need to improve the detection, treatment and control of hypertension among older adults in the LAC region. 2,10,45 Among respondents with hypertension, awareness was high (> 80%) in both countries; awareness was slightly higher among Brazilian than Colombian respondents.…”
Section: Discussionmentioning
confidence: 99%